Does Size Matter? Examining the Role of Firm Size in the Relationship Between Previous Audit Opinions and Going Concern Audit Quality - Edi Triwibowo; Ahmad Bukhori Muslim; Altaf Agil Aditya Putra (Jurnal Akuntansi Bisnis Pelita Bangsa, 2025)
This study investigates the influence of company size, solvency, and profitability on going-concern audit opinions and examines the moderating role of audit firm size. Data from 72 firm-year observations of manufacturing companies listed on the Indonesia Stock Exchange (2022–2024) were analyzed using logistic regression. The results show that company size has a significant negative effect on going-concern audit opinions, while solvency and profitability do not have significant direct effects. However, audit firm size significantly strengthens the relationship between profitability, solvency, and company size with going-concern opinions. The findings confirm that auditors’ judgments are influenced not only by financial performance but also by auditor capacity and independence. This study contributes to the audit quality literature by integrating firm-specific and auditor-specific determinants of going-concern evaluations in emerging markets.